Penerapan Computer Mediated Communication Mobile Application Mall Sampah Sebagai Layanan Penjemputan Sampah di Era Digital - Nadya Ananda Rezky Ichwan (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Mall Sampah is present as a solution in effective and efficient waste management that seeks to utilize waste, which has the advantage of added value and utilizes mobile application-based technology. The purpose of this study is to explore the application of CMC in a mobile application-based garbage collection service in the digital era. The research method used in this study uses a qualitative method with a phenomenological approach. With data collection techniques in the form of in-depth interviews with informants. The results of the study found that the application of CMC in the Garbage Mall application can fulfill three important assumptions in CMC, namely communication as a process of exchanging information, where in this application communication interactions have been built between Garbage Mall users and collectors, then mediation acts as a technology that can assist in transferring information such as the Garbage Mall application and several supporting platforms in user communication and garbage pickers such as Whatsapp Messenger, email and telephone, after that the last basic assumption is that the computer is a tool in running technology so that humans can still interact with each other such as using cell phones/ smartphone.